Análise do equilíbrio iônico no cultivo do camarão marinho Litopenaeus vannamei utilizando águas mães de salinas - Conceição, Vanderlan de Souza (Universidade Federal Rural do Semi-Árido, 2019)
Aquaculture is the science that studies techniques of cultivation in closed environment, since shrimp farming is one of the branches of aquaculture whose main objective is the creation of prawns in captivity. The present work had as main objective to analyze the best ionic balance for the zootechnical performance of the shrimp Litopenaeus vannamei, with the use in different saline concentrations using mother waters. The experiment was carried out in the Aquaculture sector of the Federal Rural Semi-Arid University-UFERSA, in the municipality of Mossoró-RN. The experimental design was completely randomized (DIC), with five treatments and four replications, totaling twenty experimental units. In relation to the physical-chemical parameters of the water, these were checked weekly, being evaluated the temperature, dissolved oxygen, pH, salinity and conductivity. We used 20 boxes with dimensions of 55cm length, 47cm width and 30cm depth, with the boxes filled with 30 liters of water. In the experimental units, the prawns were fed three times a day. Data regarding final biomass, final mean weight, survival, and FCAA, as well as water quality parameters, were submitted to ANOVA one-way analysis of variance. In relation to the physicochemical analyzes of water, no significant differences were found in the parameters of temperature, pH and dissolved oxygen. In the treatments related to the final mean weight, final biomass, FCAA and survival, considerable differences were found. Therefore, it is possible to conclude that it is not possible to grow L. vannamei by raising the salinity to 4 and 6 ppt, adding mother water with 460 ppt saline concentration as a function of the ionic imbalance.
Monografia
Keywords: Água mãe; Concentração iônica; L. vannamei; Mother water; Lon concentration; L. Vannamei; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA